Возрастные морфо-функциональные изменения репродуктивной системы самок клеща Varroa jacobsoni - Акимов, И.А.; Пилецкая, И.В.; Ястребцов, А.В. (Вестник зоологии, 1988)
Целью настоящей работы было изучение динамики изменений морфологии и функции репродуктивной системы самок при подготовке к размножению и при активном размножении в расплоде хозяина, а также углубление наблюдений за яйцекладкой. During life period, female reproductive system shows non-reciprocable morphological age changes, that considerably limit its reproductive capacity. Synchronization of the Varroa age changes with developmental stages of the host (honey bee) goes along with periods of intense oocytes development in ovaries, high vitellogenesis intensity, considerably high embryo development tempo (not exceeding 30 hrs), parallel development within reproductive system of two eggs. Disbalancement of these processes leads to nonviable ova appearance (type I and II), and non fertile females. Female reproductive capacity is realized during extremely short time (5 to 6 days). Under some conditions female may visit brood some times.